Compatibilização de projetos em edifícios de múltiplos andares: estudo de caso - Sousa, Francisco Jesus de (2010)
The high levels of waste in the construction industry in Brazil reduce significantly the profit margins of entrepreneurs. The overestimation of the systems, stops and rework due to interferences between projects, missing or incorrect information, employment of non-standard materials and greater use of skilled manpower for the lack of constructability are factors related to the cost of waste caused by a lack or rationalization and project coordination. In this context, the project presents itself as essential, due to the great need in the construction industry to improve project design to optimize and add values to the enterprise. This research has as main objective to study and diagnose the process of development and compatibility of project in multi-floors building in the Petrolina-PE e Juazeiro-BA. The author uses the qualitative research through field research and analysis of incompatibility in the project through a case study. The qualitative research aims to identify the procedures employed in the development of projects accordance to the graphical representation, alignment of projects, CAD technologies and information technology. The analysis of case studies are performed through the architectural and complementary projects, aiming accordance, standardization and compatibility of building elements in buildings with multiples floors. The findings presented in this paper show a diagnosis of process of development and compatibility of projects in buildings with multiple floors. Promoting reflection on a number of relevant issues with an emphasis on reducing waste in construction and evaluation that led to the disclosure of endogenous and exogenous obstacles in the process of compatibility project